Pengaruh Kemampuan Kerja dan Disiplin kerja Terhadap Kinerja Pegawai Kecamatan Ganding Kabupaten Sumenep Yang Dimediasi Oleh Profesionalisme - Nurul Yaqien; Chamariyah; C. Sri Hartati (Fakultas Ekonomi Universitas 45 Surabaya, 2022)
Nurul Yaqien, 2022. The Effect Of Work Ability And Work Discipline On The Performance Of Employees In Ganding District, Sumenep Regency Mediated By Professionalism. Postgraduate Program at Wijaya Putra University, Surabaya. This type of research is explanatory research, the approach used is a quantitative approach with a total sample of 64 employees. The purposes of this study are 1) To examine and analyze the significant effect of work ability on the performance of employees in Ganding District, Sumenep Regency. 2) To test and analyze the significant effect of work ability on the professionalism of the employees of Ganding District, Sumenep Regency. 3) To test and analyze the significant effect of work discipline on the professionalism of employees in Ganding District, Sumenep Regency. 4) To test and analyze the significant effect of work discipline on the performance of employees in Ganding District, Sumenep Regency. 5) To test and analyze the significant effect of employee professionalism on employee performance in Ganding District, Sumenep Regency. 6) To test and analyze the significant effect of work ability on the performance of Ganding District employees, Sumenep Regency mediated by professionalism. 7) To test and analyze the significant effect of work discipline on the performance of Ganding District employees, Sumenep Regency mediated by professionalism.